Joint Access Control and Subchannel Allocation Scheme for Femtocell-Based M2M Network Using a Truthful Mechanism - Chengmei Li; Jianjun Wu; Ziqiang Feng; Xi Luan; Haige Xiang (International Journal of Distributed Sensor Networks)
A joint access control and subchannel allocation (JACSA) scheme is proposed in this paper for femtocell-based machine-to-machine (M2M) network to provide better communication services. As short-range and cost-beneficial eNodeBs, femtocells can improve indoor coverage and data transmission, and can further be used for M2M communication. There are two challenges for femtocell network, access control and truth-telling. Femtocell machine-type communication devices (FMD) select femtocell access points (FAPs) according to the reported channel capacities, while the true values are private information of each femtocell. Therefore, selfish FAPs have incentive to report larger capacities to win greater opportunity to be selected. To solve the aforementioned two problems, a JACSA scheme based on the Arrow-d'Aspremont-Gerard-Varet (AGV) is proposed both in open access and hybrid access scenarios, and formula derivations are given. We prove that, compared with the optimal subchannel allocation (OSA) scheme, JACSA scheme has the feature of achieving near optimal performances with much lower computational complexity. Furthermore, we compare the allocation results for open access and hybrid access in the proposed JACSA scheme. Finally, simulations are performed, and the results verify the availability of our proposed scheme.